2013
DOI: 10.1007/s13205-013-0153-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of relevant non-target organisms exposed to weevil-resistant Bt sweetpotato in Uganda

Abstract: Assessment of the impact of transgenic crops on non-target organisms (NTO) is a prerequisite to their release into the target environment for commercial use. Transgenic sweetpotato varieties expressing Cry proteins (Bt sweetpotato) are under development to provide effective protection against sweetpotato weevils (Coleoptera) which cause severe economic losses in sub-Saharan Africa. Like any other pest control technologies, genetically engineered crops expressing insecticidal proteins need to be evaluated to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As examples, Cry2Aa (formerly CryB1) is active against insects from the orders Lepidoptera and Diptera (mosquitoes) [22, 23, 58], while Cry3Aa displays activity against insects from the orders Coleoptera, Hemiptera, and Hymenoptera [58]. It is important to know that this cross-order activity does not impact the environmental safety of Bt -based products as Cry proteins tend be highly toxic to one order or closely related orders (primary specificity range), but much less toxic to distantly related taxa [36, 58, 59]. This pattern of activity was observed for the Cry51Aa2.834_16 protein where high toxicity or protection from feeding damage was shown against some hemipterans and thysanopteran species (primary specificity range), but relatively weak toxicity was shown against distantly related Coleoptera species.…”
Section: Discussionmentioning
confidence: 99%
“…As examples, Cry2Aa (formerly CryB1) is active against insects from the orders Lepidoptera and Diptera (mosquitoes) [22, 23, 58], while Cry3Aa displays activity against insects from the orders Coleoptera, Hemiptera, and Hymenoptera [58]. It is important to know that this cross-order activity does not impact the environmental safety of Bt -based products as Cry proteins tend be highly toxic to one order or closely related orders (primary specificity range), but much less toxic to distantly related taxa [36, 58, 59]. This pattern of activity was observed for the Cry51Aa2.834_16 protein where high toxicity or protection from feeding damage was shown against some hemipterans and thysanopteran species (primary specificity range), but relatively weak toxicity was shown against distantly related Coleoptera species.…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan agriculture the use of transgenic Bt sweetpotato is viewed as an attractive alternative to the slower conventional breeding for host-plant resistance as well as to other pest management options which some consider to be too expensive for smallholder farmers to use (Rukarwa et al, , 2014. Other research using Bt protein expression in sweetpotato has taken place in Cuba (Morán et al, 1998), China (Yang et al, 2011) and India (Shekhar et al, 2013).…”
Section: Host-plant Resistancementioning
confidence: 99%
“…Moreover, the efficiency of different Bacillus thuringiensis insecticidal proteins in controlling Cylas spp. has been previously shown (Morán et al, 1998;Ekobu et al, 2010;Rukarwa et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
“…larvae (Ekobu et al, 2010). Accordingly, it has been demonstrated that coleopteran-active Cry proteins; Cry3Aa3, Cry3Bb3, Cry3Ca1, Cry7Aa1, and Cry23Aa/Cry37Aa proteins are toxic for different sweet potato weevil species (Morán et al, 1998;Ekobu et al, 2010;Rukarwa et al, 2014). More attention has been directed toward the 3-domain group of insecticidal Cry proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation